Differences in Skills Before and After Being Given Health Education Using Audiovisual About First Aid Burns in Students MA Raudlatus Syabab - Darotin, Rida; Hasanah, Tiaratul (LPPM Universitas dr. Soebandi, 2024)
Introduction: Burns are an emergency problem that can occur anytime and anywhere, both minor, moderate and severe burns. Burns require proper treatment from the beginning of the wound incident. There are still many actions in providing first aid for burns that are not appropriate. Based on the results of a preliminary study at MA Raudlatus Syabab, as many as 80% of 10 students have experienced burns such as chemical contamination, scalded etc. Research Objectives: The purpose of this study was to determine the differences in skills before and after being given health education using audiovisual about first aid burns in MA Raudlatus Syabab students. Methods: Pre-experimental research design with One group pre-post test design approach. The research population of MA Raudlatus Syabab class X students with a total of 37 people and a sample used 34 respondents. Purposive sampling technique is used. The measuring instrument uses an observation sheet and is analyzed using the Wilcoxon test. Results: The average score of students' skills in practicing first aid for burns before being given health education was 32.24. While the skills of students after being given health education are with an average score of 81.71. The difference in average score before and after health education was 49.47. The results of the Wilcoxon test obtained P-values (0.000) < α (0.05), so the conclusion was that there were differences in positive skills from the category of less skilled to very skilled in students after being given health education using audiovisual about first aid burns. Conclusions: cooperation with health authorities is needed to become one of the learning media for students to improve their knowledge and ability to provide first aid for burns.